Diversity in olfactory bulb size in birds reflects allometry, ecology, and phylogeny - Corfield, Jeremy R.; Price, Kasandra; Iwaniuk, Andrew N.; Gutierrez-Ibañez, Cristian; Birkhead, Tim; Wylie, Douglas R. (Frontiers in Neuroanatomy, 2015)
The relative size of olfactory bulbs is correlated with olfactory capabilities across vertebrates and is widely used to assess the relative importance of olfaction to a species’ ecology. In birds, variations in the relative size of olfactory bulbs are correlated with some behaviors, however, the factors that have led to the high level of diversity seen in olfactory bulb sizes across birds are still not well understood. In this study, we use the relative size of olfactory bulbs as a neuroanatomical proxy for olfactory capabilities in 135 species of birds, representing 21 orders. We examine the scaling of olfactory bulbs with brain size across avian orders, determined likely ancestral states and test for correlations between OB sizes and habitat, ecology and behavior. The size of avian OBs varied with the size of the brain and this allometric relationship was for the most part isometric, although species did deviate from this trend. Large olfactory bulbs were characteristic of more basal species and in more recently derived species the OBs were small. Living and foraging in a semi aquatic environment was the strongest variable driving the evolution of large olfactory bulbs in birds; olfaction may provide cues for navigation and foraging in this otherwise featureless environment. Some of the diversity in OB sizes was also undoubtedly due to differences in migratory behavior, foraging strategies and social structure. In summary, relative OB size in birds reflect allometry, phylogeny and behavior in ways that parallel that of other vertebrate classes. This provides comparative evidence that supports recent experimental studies into avian olfaction and suggests that olfaction is a critically important sensory modality for all avian species.